Efficient rates for water for agricultural use in the Comarca Lagunera - Ramirez Barraza, Brenda Aracely; Estrada, Adrian Gonzalez; Valdivia Alcalá, Ramón; Salas González, José María; García Salazar, José Alberto (Revista Mexicana de Ciencias Agrícolas, 2019)
Water is an increasingly scarce resource and therefore has an increasing importance for society, which is why it is pertinent and necessary to determine its economic price. The objectives of this research were to determine the shadow price of agricultural water supplied by gravity irrigation and pumping in the Lagunera Region (Coahuila and Durango), in order to calculate the efficient rates, which induce an optimal economic use of the resource. A linear programming model with restrictions on availability of labor, land and water was used. Different scenarios of decreasing water availability were analyzed in order to study the behavior of its shadow price in the face of changes in the amount available. The results indicate that the water shadow price is 1.56 m-3 MN for pumping and 0.91 m-3 MN for gravity. It was concluded that the fees paid for irrigation water in the region are considerably lower than the opportunity cost or shadow price of water. It was also concluded that the current allocation of water for agricultural use generates an inefficient crop pattern, as it is used to produce alfalfa and other forages, which do not appear in the optimal crop pattern calculated with the linear programming model built for the region. It is recommended that the rates be defined taking as reference the shadow price of water, which should be adjusted according to the periodic changes in the water scarcity level.